Methods and applications of linear models regression and the analysis of variance - Hocking, R. R. (Ronald R.), 1932-; ebrary, Inc. (Hoboken, N.J. : Wiley, 2013)
"The new edition of this "essential desktop reference book. [that] should definitely be on your bookshelf" (Technometrics) features a newly reorganized approach to linear regression that promotes the understanding of theory and models concurrently, featuring newly-developed topics in the field and the use of software applications. It includes numerous exercises; graphics and computations developed using JMP software; a new chapter on recent developments with the distribution of linear and quadratic forms; and new topical coverage of least squares, the cell means model, and more"--
pt. 1. Regression -- pt. 2. The analysis of variance.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Regression analysis; Analysis of variance; Linear models (Statistics); Electronic books